2016
DOI: 10.1016/j.enconman.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic shape optimization of non-straight small wind turbine blades

Abstract: Small wind turbines usually operate in sub-optimal wind conditions in order to satisfy the demand where it is needed. The aerodynamic performance of small horizontal axis wind turbines highly depends on the geometry. In the present study, the geometry of wind turbine blades are optimized not only in terms of the distribution of the chord and twist angle but also with 3-dimensional stacking line. As the blade with 3-dimensional stacking line is given sweep in the plan of rotation and dihedral in the plan contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 50 publications
0
19
0
2
Order By: Relevance
“…The author of this study compared the design of a rotor blade with a straight, ±10% (forward or backward) sweep, dihedral and winglet and concluded that the aerodynamic performance is, in general, enhanced by these tip modifications, although the trends differ between the forward and backward orientations. Shen et al (2016) studied an aerodynamic shape optimization of non-straight small wind turbine blades where they attempted to optimize the annual energy production and the starting performance of HAWTs. According to these results, the wind turbine blades with a properly designed 3-dimensional stacking line can increase the annual energy production and have a better starting behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The author of this study compared the design of a rotor blade with a straight, ±10% (forward or backward) sweep, dihedral and winglet and concluded that the aerodynamic performance is, in general, enhanced by these tip modifications, although the trends differ between the forward and backward orientations. Shen et al (2016) studied an aerodynamic shape optimization of non-straight small wind turbine blades where they attempted to optimize the annual energy production and the starting performance of HAWTs. According to these results, the wind turbine blades with a properly designed 3-dimensional stacking line can increase the annual energy production and have a better starting behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al . optimized the geometry of wind turbine blades in terms of the distribution of the chord and twist angle with 3‐dimensional stacking line. They used Lifting Line Surface method with Free Wake model as the aerodynamic model.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the optimized mathematical model of the airfoils was established by combining Genetic Algorithm method and the flow solver RFOIL. Shen et al [20] optimized the geometry of wind turbine blades in terms of the distribution of the chord and twist angle with 3-dimensional stacking line. They used Lifting Line Surface method with Free Wake model as the aerodynamic model.…”
Section: Introductionmentioning
confidence: 99%
“…The 20year fatigue life (calculated using Miner's rule) was also incorporated as a constraint on the designs. In addition to structural optimisation, studies of wind turbine blades often investigate the aerofoil and blade geometric variables to improve the power production capacity and aerodynamic performance of the turbine [15] to [17]. The scope of the optimisation problem can be expanded to investigate the coupled aero-elastic behaviour of novel blade designs (e.g.…”
Section: Introductionmentioning
confidence: 99%